CONSUMERS' BEHAVIOURAL INTENTION TO ADOPT SHARI’AH-COMPLIANT DIGITAL GOLD PLATFORM IN MALAYSIA: EXTENSION OF UTAUT MODEL - Hamdan, Nur Hazirah binti; Kassim, Salina binti; Nik Azman, Nik Hadiyan; Abd Rahman, Noor Amira Syazwani Binti (Journal of Islamic Monetary Economics and Finance, 2025)
The advancement of technology has resulted in the emergence of digital platforms, such as digital gold platforms, as alternative channels for retail investment. In this study, we investigate factors that influence consumers’ behavioural intentions towards a Shari’ah-compliant digital gold platform in Malaysia. The study incorporates trust and Shari’ah-compliance as constructs in the extended UTAUT model. Gathering data from 130 respondents and applying SmartPLS 4.0 for data analysis, the study documents the significance of performance expectancy, effort expectancy, trust, and Shari’ah-compliance. Meanwhile, facilitating conditions and social influence turn out to be insignificant. The study notes that feeling safe, secure, and transparent as well as having Shari’ah-compliant features are crucial factors that influence consumer intention to adopt the Shari’ah-compliant digital gold platform in Malaysia. It is also critical to be aware of the services provided by Shari’ah-compliant providers and financial institutions by utilising the social network within the Shari’ah-compliant finance sphere. ACKNOWLEDGEMENT The second author (Nik Hadiyan Nik Azman) would like to Acknowledge “Ministry of Higher Education Malaysia for Fundamental Research Grant Scheme with Project Code: FRGS/1/2021/SS01/USM/03/1”.